LEGAL PROTECTION OF TRADITIONAL ARCHITECTURAL DESIGN OF KAMPUNG NAGA AS TRADITIONAL KNOWLEDGE IN INDONESIA - Maya Ruhtiani (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2021)
Legal protection of traditional architectural design as a part of Indonesian traditional knowledge, without being realized, has become a great and complicated issuebecause recently it is being exploited by irresponsible parties. The Indonesian philosophy Bhinneka Tunggal Ika describes Indonesia which consists of many ethnic groups around every corner of archipelago in which they create their own culture area with different condition. Every ethnic has traditional architecture as the cultural manifestation which rests on the custom and belief. Traditional architectural design as a piece of traditional knowledge in Indonesia is considered as one of cultural conservation which is material that needs to be protected. One of the matters that attracts attention now is architectural design of indigenous village in Indonesia called Kampung Naga. Kampung Naga provides sample or design of energy-efficient building in which its design is later developed by the private parties in Indonesia. Traditional intellectual property specifically the local wisdom has proved to offer many contributions for the development of environmental insight by using the teachings from ancestors which have been inherited through generations for centuries. Therefore, this research focuses on legal protection of traditional architectural design as a cultural conservation of Kampung Naga society in Indonesia which needs to be protected from exploitation or piracy both from private companies in Indonesia and from another country.